Participation in WTO Dispute Settlement : Complainants, Interested Parties, and Free Riders - Bown, Chad P. (Published by Oxford University Press on behalf of the World Bank, 2014)
What affects a country's decision of whether to formally engage in a trade dispute directly related to its exporting interests? This article empirically examines determinants of affected country participation decisions in formal trade litigation arising under the World Trade Organization (WTO) between 1995 and 2000. It investigates determinants of nonparticipation and examines whether the incentives generated by the system's rules and procedures discourage active engagement in dispute settlement by developing country members in particular. Though the size of exports at stake is found to be an important economic determinant affecting the decision to participate in challenges to a WTO-inconsistent policy, the evidence also shows that measures of a country's retaliatory and legal capacity as well as its international political economy relationships matter. These results are consistent with the hypothesis of an implicit 'institutional bias' generated by the system's rules and incentives that particularly affects developing economy participation in dispute settlement.